Constraints Perceived in Using Livestock-based Mobile Applications by Dairy Farmers in Uttar Pradesh - Rawat, Umashankar; Singh, Sanjeev Kumar; Singh, Amit; Khandait, Vivek; Rashmi (International Journal of Livestock Research, 2025)
The present study was conducted in the Mathura district of Uttar Pradesh to identify the farmers' constraints in using livestock-oriented mobile applications for getting animal husbandry information and the perceived need for mobile applications to overcome these constraints. 150 dairy farmers were randomly chosen from 10 villages across five blocks. Information was gathered through a pre-designed interview schedule and focus group discussions aligned with the study objectives. The collected data were analyzed using appropriate statistical tools. The study revealed that lack of updated technology ranked first among infrastructure constraints. The inability to operate applications and their complexity is the most perceived constraint among technical constraints. Inadequate awareness of applications is the highest constraint, followed by a lack of encouragement and unwillingness to learn socio-personal constraints.